Processus territoriaux et gestion de l’eau en Camargue gardoise - Daniel Petit; Anne Rivière-Honegger (Développement Durable et Territoires)
Next to the major changes which occurred in the « Camargue gardoise » during sixties and seventies, and because of the becoming obsolete « Traité des Marais » which was regulating the collective management of water levels, the economic actors dealing with water concerns have been developing individualistic policies. Water has became a source of many conflicts implying serious consequences on resources and natural spaces. The achievement of an environmental chart and of a « SAGE » at the beginning of the nineties were the ground baits for a come back to a collective form of water management. However, it’s a long way to consider water as a vector of territorial construction thanks to collective agreements about projects dealing with water. In the following context, the 2002 and 2003 floods have revealed territorial limitations to manage this kind of crisis. They have shown that the water policies have to take inot more seriously the structural links between the different areas of decision and solidarity.